Preparation and Properties of Nanocellulose from Organosolv Straw Pulp - V. A. Barbash; O. V. Yaschenko; O. M. Shniruk (Nanoscale Research Letters, 2017)
Abstract The object of this work is to present a study of nanocellulose preparation from organosolv straw pulp (OSP) and its properties. OSP was obtained through thermal treatment in the system of isobutyl alcohol–H2O–KOH–hydrazine followed by processing in the mixture of acetic acid and hydrogen peroxide for bleaching and removal of residual non-cellulosic components. We have obtained nanocellulose from OSP through acid hydrolysis with lower consumption of sulfuric acid and followed by ultrasound treatment. The structural change and crystallinity degree of OSP and nanocellulose were studied by means of SEM and XRD techniques. It has been established that nanocellulose has a density up to 1.3 g/cm3, transparency up to 70%, crystallinity degree 72.5%. The TEM and AFM methods shown that nanocellulose have diameter of particles in the range from 10 to 40 nm. Thermogravimetric analysis confirmed that nanocellulose films have more dense structure and smaller mass loss in the temperature range 220–260 °C compared with OSP. The obtained nanocellulose films had high Young’s modulus up to 11.45 GPa and tensile strength up to 42.3 MPa. The properties of obtained nanocellulose from OSP exhibit great potential in its application for the preparation of new nanocomposite materials.